2020
DOI: 10.1177/8755293020919424
|View full text |Cite
|
Sign up to set email alerts
|

Household adjustment to seismicity in Oklahoma

Abstract: Earthquakes have manifested as a slow-onset hazard for the state of Oklahoma. While this shaking is resulting in considerable damage, we know little about how residents understand or are adjusting to this new hazard. To explore this issue, we deployed a survey in two Oklahoma communities with varying levels of earthquake exposure and experience to better understand the adjustments, such as purchasing earthquake insurance or installing earthquake latches, residents are intending to undertake within these commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…People are more likely to take precautionary measures and disaster preparedness behaviors when they believe they can do it. In studies based on other theories and behavior change models, people with higher self-efficacy performed more preventive actions and disaster preparedness behaviors ( 22 , 31 , 41 , 50 52 ). According to a study by Newnham in Hong Kong ( 53 ), people with higher self-efficacy had fewer evacuation barriers during disasters.…”
Section: Discussionmentioning
confidence: 99%
“…People are more likely to take precautionary measures and disaster preparedness behaviors when they believe they can do it. In studies based on other theories and behavior change models, people with higher self-efficacy performed more preventive actions and disaster preparedness behaviors ( 22 , 31 , 41 , 50 52 ). According to a study by Newnham in Hong Kong ( 53 ), people with higher self-efficacy had fewer evacuation barriers during disasters.…”
Section: Discussionmentioning
confidence: 99%
“…In Ning et al's study in China (2021), people with higher self-efficacy had more emergency preparedness behavior ( 8 ). In a study by Greer et al in the United States (2020), it has been shown that the higher the self-efficacy of individuals, the higher their intention to prepare ( 30 ). People are likely to engage in preventive and disaster preparedness behaviors if they are confident in their ability to perform actions.…”
Section: Discussionmentioning
confidence: 99%
“…Although hazard intrusiveness is mentioned in PADM (Lindell, 2018), it is seldom included in disaster response studies. Instead, this idea is mostly included in hazard adjustment studies, with researchers finding that hazard intrusiveness could affect people's CRP (Greer et al, 2020;Lindell, 1994Lindell, , 2013Wu, Greer, et al, 2017) and ARP (Weinstein et al, 2000). A recent study also found hazard intrusiveness significantly predicts a latent CRP variable that is constructed by using four CRP1 variables (perceived likelihood of potential damage to their homes or properties, injuries, job disruptions, and daily routine disruptions) (Li et al, 2023).…”
Section: Relationships Among Perceived Threat Variablesmentioning
confidence: 99%